1999
DOI: 10.21236/ada360577
|View full text |Cite
|
Sign up to set email alerts
|

Directory of Industry and University Collaborations with a Focus on Software Engineering Education and Training, Version 7

Abstract: The ideas and findings in this report should not be construed as an official DoD position. It is published in the interest of scientific and technical information exchange.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Such collaborations have attracted widespread attention because the rapidly changing business environment demands industries to continuously enhance their efficiency and productivity (Perkmann et al , 2011; Thursby et al , 2009). Moreover, Beckman (1997) indicated that the escalating costs of equipping employees with necessary skills, knowledge and abilities have pushed the necessity for strong partnerships between universities and industries. Such efforts have shown that the cooperation between the two worlds started to gain bigger momentum (Motohashi, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Such collaborations have attracted widespread attention because the rapidly changing business environment demands industries to continuously enhance their efficiency and productivity (Perkmann et al , 2011; Thursby et al , 2009). Moreover, Beckman (1997) indicated that the escalating costs of equipping employees with necessary skills, knowledge and abilities have pushed the necessity for strong partnerships between universities and industries. Such efforts have shown that the cooperation between the two worlds started to gain bigger momentum (Motohashi, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the e-mail addresses came from SEI's published software engineering education directories. 6,7 In most cases, however, e-mail addresses were extracted from instructors' homepages using the readily available Table 1…”
Section: Survey Methodologymentioning
confidence: 99%
“…The WGSEET reports indicate worldwide interest in industry-academic collaborative work. From these reports and other published work [8,9,10] it would appear that the predominant form of this collaboration involves universities delivering specialized training to industrial partners [4,5] . Another popular form of collaboration involves students doing projects given by industrial partners as part of their academic program [2,15] .…”
Section: Industry-academia Collaborationmentioning
confidence: 96%